PENGELOLAAN SAMPAH LINGKUNGAN BERBASIS MASYARAKAT SEBAGAI PILOT PROJECT PENGELOLAAN SAMPAH PADA PERUMAHAN NASIONAL SIMALINGKAR MEDAN - Dharma Sembiring; Erna Frida; Imanuel P. Tua Panggabean (Universitas Quality, 2018)
National Housing (Perumnas) Simalingkar Medan is a residential area that is quite dense with residents around 8,628 households. Until now, the garbage produced by households has not been managed properly, this can be seen from the large amount of garbage that has accumulated in several corners of settlements, in the banks and sideways / riverbanks even in the watershed in the settlements.Waste management at Perumnas Simalingkar Medan still uses a conventional treatment system, which starts from the collection process from a container or household garbage collection place, then transports it to a temporary collection point (TPS) which is also called the transfer depot in the settlement on Sawit Raya road, then transported to the final processing site (TPA) in the village of Namo Bintang. It has been designed a counter that can be used to count household waste and be used as a planting medium that can be marketed by plant entrepreneurs.